Fitting in or Sticking Together: The Prevalence and Adaptivity of Conformity, Relatedness, and Autonomy in Japan and Turkey - (:unkn) unknown (SAGE PUBLICATIONS INC, 2014)
In this research, we compare two forms of interdependent agency. Whereas all interdependent cultures emphasize interpersonal connectedness, we suggest that the nature of this connection may differ between face and honor cultures. In a large survey, with 163 Japanese and 172 Turkish students, we tested the idea that, consistent with the concern for face, Japanese interdependence emphasizes conformity; that is, fitting in, whereas, consistent with the concern for honor, Turkish interdependence stresses relatedness; that is, sticking together. The results confirmed these hypotheses: Japanese described their agency more in terms of conformity than Turks, whereas Turks described their agency more in terms of relatedness. Moreover, relational well-being was predicted by conformity in the Japanese group and by relatedness in the Turkish group. Autonomy was also important for both samples, and it predicted personal well-being. Results suggest that a multi-dimensional approach to interdependent agency is needed to distinguish meaningfully between different interdependent cultures.
Keywords: cultural models of agency; self-construal; face culture; honor culture; Japanese culture; Turkish culture; conformity; relatedness; autonomy; NORTH-AMERICAN; UNITED-STATES; SELF; IDENTITY; CULTURE; HARMONY; INDEPENDENCE; CONSTRUCTION; SATISFACTION; PARENTS